Personal AI Companion Voice Assistant - Keshava Gowtham NS; Deepak V Ingale; Harshitha N; Adithya S; Nithish Rao H D; V Venkatesh (International Journal of Engineering and Management Research, 2024)
This paper presents the design and implementation of a personal AI companion voice assistant leveraging the ESP32 microcontroller platform. The system incorporates advanced AI algorithms for natural language processing and voice recognition, enabling intuitive user interaction. Through seamless integration with smart devices, the assistant enhances user experience while prioritizing data privacy and security. The project contributes to the evolution of IoT technologies by offering a personalized and intelligent voice assistant solution.